11, 12 -Epoxyeicosatrienoic acid (11, 12 EET) reduces excitability and excitatory transmission in the hippocampus. (1st September 2017) - Mule, Nandkishor K.; Orjuela Leon, Anette C.; Falck, John R.; Arand, Michael; Marowsky, Anne
Abstract: Recent studies suggest a role for the arachidonic acid-derived epoxyeicosatrienoic acids (EETs) in attenuating epileptic seizures. However, their effect on neurotransmission has never been investigated in detail. Here, we studied how 11, 12- and 14, 15 EET affect excitability and excitatory neurotransmission in mouse hippocampus. 11, 12 EET (2 μM), but not 14, 15 EET (2 μM), induced the opening of a hyperpolarizing K + conductance in CA1 pyramidal cells. This action could be blocked by BaCl2, the G protein blocker GDPβ-S and the GIRK1/4 blocker tertiapin Q and the channel was thus identified as a GIRK channel. The 11, 12 EET-mediated opening of this channel significantly reduced excitability of CA1 pyramidal cells, which could not be blocked by the functional antagonist EEZE (10 μM). Furthermore, both 11, 12 EET and 14, 15 EET reduced glutamate release on CA1 pyramidal cells with 14, 15 EET being the less potent regioisomer. In CA1 pyramidal cells, 11, 12 EET reduced the amplitude of excitatory postsynaptic currents (EPSCs) by 20% and the slope of field excitatory postsynaptic potentials (fEPSPs) by 50%, presumably via a presynaptic mechanism. EEZE increased both EPSC amplitude and fEPSP slope by 40%, also via a presynaptic mechanism, but failed to block 11, 12 EET-mediated reduction of EPSCs and fEPSPs. This strongly suggests the existence of distinct targets for 11, 12 EET and EEZE in neurons. In summary, 11, 12 EET substantially reduced excitation in CA1 pyramidal cells by inhibiting the release of glutamate and opening a GIRK channel. These findings might explain the therapeutic potential of EETs in reducing epileptiform activity. Highlights: 11, 12 EET hyperpolarizes CA1 pyramidal cells by activating a GIRK channel. Both 11, 12 and 14, 15 EET inhibit glutamate release onto these cells. These effects may explain the therapeutic potential of EETs in reducing epileptiform activity. The functional antagonist EEZE does not block EET effects in CA1 pyramidal cells.